Implementation of integrated quality management in Private Islamic Religious College: Case Study of Tazkia Islamic Religion Institute in Jakarta - Marjuki, Marjuki; Saud, Udin Saepudin; Andriyani, Andriyani; Fahrudin, Adi (Technium Social Sciences Journal, 2021)
This study aims to determine: 1) the planning of the implementation of integrated quality management at the Tazkia Islamic Institute. 2). Implementation and implementation Implementation of integrated quality management at the Tazkia Islamic Institute. 3). Analysis and evaluation of the implementation of integrated quality management at the Tazkia Islamic Institute. This research uses case study method, data collection is done through interviews, observation and review of documents, data sources obtained through informants, photos and documents. Data analysis uses data reduction techniques, data display and verification/conclusion. The results of this study indicate that 1). Integrated quality management planning at the Tazkia Islamic Institute begins with mapping the condition of the institution and conducting an analysis to map the institution with the principles of CITB (fast, coordinated, complete, quality). 2). The implementation of integrated quality management is carried out after going through a measurable planning process by preparing management financing and human resource support capacity, implementation begins with the following steps: implementing quality management with administrative processes so that it can implement management of higher education as a whole, developing the concept of quality integration with standard learning processes and curricula, linking integrated quality management with university research processes high level, synergizing academic processes by equating the vision and mission of the institution. 3). Supervision of the implementation of quality management at the Tazkia Islamic Institute is carried out by the chancellor by involving other university leaders, namely the vice-chancellor, directors, deans and heads of study programs, and division heads.